The Rupture of the Rectus Abdominis Muscle: An Atypical Abdominal Pain - Tuğra Yanık,; Burcu Yanık,; Mehmet Yörübulut, (Archives of Rheumatology, 2006)
The rupture of the rectus abdominis muscle is rare in sedantary people. Clinically, pain in the lower abdominal region and localized tenderness can be obtained. These patients are incorrectly sent to different specialists, and are exposed to unnecessary invasive examinations and treatments. A patient is presented here with low abdominal pain which began after a football match and later was diagnosed as rupture in the rectus abdominis muscle and this case is discussed with in literature. (Rheumatism 2006; 21: 111-3)